2005
DOI: 10.1039/b501446h
|View full text |Cite
|
Sign up to set email alerts
|

On the Diels–Alder reactions of pentadienyl maleates and citraconates

Abstract: Reactions between conjugated dienols and maleic anhydride provide either cis-fused or trans-fused bicyclic products as major products, depending upon how the reaction is carried out. Simply mixing the two reactants together generally leads to cis-fused lactone acids in thermal reactions which proceed viaintermolecular Diels-Alder reaction followed by intramolecular esterification. Pre-forming the maleate half ester derivative followed by heating affords predominantly trans-fused lactone acids in good yields by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…The cis-fused isomers, resulting from the intermolecular Diels-Alder pathway, are the dominant products but the trans-fused bicycles, accounting for about 10% of the product mixture, result from the competing esterification-IMDA pathway (Scheme 1). 6 Nevertheless, we observe a level of p-diastereofacial selectivity between the two cis-isomers that is consistent with the earlier report.…”
Section: Figsupporting
confidence: 93%
See 1 more Smart Citation
“…The cis-fused isomers, resulting from the intermolecular Diels-Alder pathway, are the dominant products but the trans-fused bicycles, accounting for about 10% of the product mixture, result from the competing esterification-IMDA pathway (Scheme 1). 6 Nevertheless, we observe a level of p-diastereofacial selectivity between the two cis-isomers that is consistent with the earlier report.…”
Section: Figsupporting
confidence: 93%
“…We recently showed that reactions between conjugated dienols 1 and maleic anhydride 2 (Scheme 1) provide either cis-fused 5 or trans-fused 6 bicyclic products as major products, depending upon how the reaction is carried out. 6 When mixtures of the two reactants are heated, an endo-selective intermolecular Diels-Alder reaction gives putative hydroxy anhydride intermediate 3, which rapidly undergoes intramolecular esterification to furnish Scheme 1 cis-fused lactone acids 5. Alternatively, the pre-formed maleate half-ester derivative 4 affords trans-fused lactone acids 6 in high selectivity by way of an exo-selective 5 IMDA reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction had already been reported to work well under SFC through formation of a melt (23). The stereochem-istry of the product had been established as cis (endoaddition) (24). The reaction on up to 5 mmol scale can be successfully done as a solvent-free reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Then, in the reaction between D1 and diene 3c , the product 4′cA was obtained as the only adduct in 90% yield. In this case, the cycloaddition was followed by an intramolecular lactonization occurring on cycloadduct 4cA and leading to 4′cA . X-ray crystallographic analysis on a monocrystal also confirmed the structure and the relative stereochemistry of the product in this case (Figure ).…”
Section: Resultsmentioning
confidence: 60%